- 68 Views
- Uploaded on
- Presentation posted in: General

Simplifying Algebraic Expressions

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -

= 2h + 1h + 4r + 3r + 7t + tCommutative Property of Addition

= (2 + 1)h + (4 + 3)r + (7 + 1)tDistributive Property

= 3h + 7r + 8tSimplify.

COURSE 3 LESSON 2-3

Simplify 2h + 4r + 7t + h + 3r + t.

2h+ 4r + 7t + h + 3r + t

2-3

4(b – 3) + 2b = 4b – 12 + 2bDistributive Property

= 4b + 2b – 12Commutative Property of Addition

= (4 + 2)b – 12Distributive Property

= 6b – 12Simplify.

COURSE 3 LESSON 2-3

Simplify 4(b – 3) + 2b.

2-3

7t – 2(t – 3) = 7t+ (–2)(t – 3)Add the opposite of 2(t – 3).

= 7t + [–2t – (–6)]Distributive Property

= 7t + (–2t) + 6Simplify.

= [7 + (–2)]t + 6Distributive Property

= 5t + 6Simplify.

COURSE 3 LESSON 2-3

Simplify 7t – 2(t – 3).

2-3

COURSE 3 LESSON 2-3

Simplify each expression.

1.3h + 7h

2.–13c + c

3.4y – 7 + 8y

4.1 – 6(b – 9)

10h

–12c

12y – 7

–6b + 55

2-3